Quality of life in chronic myeloid leukaemia patients after haematopoietic cell transplantation pretreated with second-generation tyrosine kinase inhibitors - Piekarska, Agnieszka; Gil, Lidia; Jakitowicz, Karolina; Prejzner, Witold; Komarnicki, Mieczysław; Hellmann, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : To was to determine the impact of chronic obstructive pulmonary disease (COPD) and active smoking on the efficacy of chemotherapy and complete blood count (CBC) in patients with non-small cell lung cancer (NSCLC). Material and methods : The retrospective evaluation included 50 patients with stage IIIB–IV NSCLC, who started cisplatin-based chemotherapy. Peripheral blood CBC values were collected for testing before chemotherapy and after the first and third cycles. Results: COPD was diagnosed in 49% of patients, while 42% of those enrolled were current smokers. Current smoking (p = 0.92) and COPD (p = 0.91) status did not affect the response to treatment. The non-COPD population presented a significantly higher pretreatment absolute lymphocyte count (ALC) than the COPD population (2.31 vs. 1.81 × 109/l; p = 0.0374). Also, only the non-COPD group demonstrated an elevated absolute monocyte count (AMC) following the first and third cycles of chemotherapy (p = 0.004). In current smokers, pretreatment values for white blood cells (WBC), absolute neutrophil count (ANC), and platelets (PLT) were higher than in the ex-smoker population (WBC 9.94 vs. 8.7 (× 109/l); p = 0.01; ANC 6.47 vs. 5.61 (× 109/l); p = 0.037; PLT 316 vs. 266 (× 109/l); p = 0.049). Ex-smokers demonstrated AMC level elevation after the first cycle of chemotherapy and PLT level elevation after the third cycle, while current smokers also demonstrated an early decrease in LMR. Conclusions : COPD and smoking induce chronic systemic inflammation and oxidative stress, which influence the results of standard laboratory tests, but do not change the response rate of lung cancer on chemotherapy.